Bayogenin 3‐O‐cellobioside confers non‐cultivar‐specific defence against the rice blast fungus Pyricularia oryzae. Issue 3 (30th October 2020) - Norvienyeku, Justice; Lin, Lili; Waheed, Abdul; Chen, Xiaomin; Bao, Jiandong; Aliyu, Sami Rukaiya; Lin, Lianyu; Shabbir, Ammarah; Batool, Wajjiha; Zhong, Zhenhui; Zhou, Jie; Lu, Guodong; et al.
Summary: Rice cultivars from japonica and indica lineage possess differential resistance against blast fungus as a result of genetic divergence. Whether different rice cultivars also show distinct metabolomic changes in response to P. oryzae, and their role in host resistance, are poorly understood. Here, we examine the responses of six different rice cultivars from japonica and indica lineage challenged with P. oryzae . Both susceptible and resistant rice cultivars expressed several metabolites exclusively during P. oryzae infection, including the saponin Bayogenin 3‐O‐cellobioside. Bayogenin 3‐O‐cellobioside level in infected rice directly correlated with their resistant attributes. These findings reveal, for the first time to our knowledge that besides oat, other grass plants including rice produces protective saponins. Our study provides insight into the role of pathogen‐mediated metabolomics reprogramming in host immunity. The correlation between Bayogenin 3‐O‐Cellobioside levels and blast resistance suggests that engineering saponin expression in cereal crops represents attractive and sustainable disease management.